Endothelial cells release microvesicles that harbour multivesicular bodies and secrete exosomes. Issue 4 (30th March 2023) - Petersen, Jennifer D.; Mekhedov, Elena; Kaur, Sukhbir; Roberts, David D.; Zimmerberg, Joshua
Abstract: Extracellular vesicles (EVs) released by endothelial cells support vascular homeostasis. To better understand endothelial cell EV biogenesis, we examined cultured human umbilical vein endothelial cells (HUVECs) prepared by rapid freezing, freeze‐substitution, and serial thin section electron microscopy (EM). Thin sections of HUVECs revealed clusters of membrane protrusions on the otherwise smooth cell surface. The protrusions contained membrane‐bound organelles, including multivesicular bodies (MVBs), and appeared to be on the verge of pinching off to form microvesicles. Beyond cell peripheries, membrane‐bound vesicles with internal MVBs were observed, and serial sections confirmed that they were not connected to cells. These observations are consistent with the notion that these multi‐compartmented microvesicles (MCMVs) pinch‐off from protrusions. Remarkably, omega figures formed by fusion of vesicles with the MCMV limiting membrane were directly observed, apparently releasing exosomes from the MCMV. In summary, MCMVs are a novel form of EV that bud from membrane protrusions on the HUVEC surface, contain MVBs and release exosomes. These observations suggest that exosomes can be harboured within and released from transiting microvesicles after departure from the parent cell, constituting a new site of exosome biogenesis occurring from endothelial and potentially additional cell types.